A Rapid Spectrophotometric Determination of Vanadium(V) and Molybdenum(VI) Using 2,2'-Dihydroxyazoxybenzenes - Thanikachalam, V.; Subramani, P.; Jayabharathi, J.; Manivarman, S.; Sureshkumar, G. (Asian Journal of Chemistry, 2016)
The photometric studies of vanadium(V) and molybdenum(VI) are carried out with 2,2'-dihydroxyazoxybenzenes (DHAB) in 50% ethanol-water medium at pH 2.4 and 1.5, respectively. The maximum absorbance occurred at 405 nm and 625 nm for vanadium-DHAB and molybdenum-DHAB systems. Beer's law is obeyed in the concentration ranging from 0-7 ppm and 0-54 ppm and molar absorptivities of the systems are 5.814 × 103 and 8.90 × 102 dm3 mol-1 cm-1 for V-DHAB and Mo-DHAB systems, respectively. The effects of foreign ions are also studied.